Intranasal Ectopic Tooth Causing Septal Deviation - Altin, Gokhan; Kersin, Burak; Guldun, Erol; Ozcelik, Necdet; Calim, Omer Faruk; ÇALIM, ÖMER FARUK (My University, 2015)
The ectopic tooth incidence is increasing gradually. The etiology could not be explained in so many cases. It is very rare for the tooth to be in a place outside the normal location, and disrupt the structure of nasal septum. The diagnosis can be made by physical examination and radiology. In our study, the case of a 5-year-old male patient, with a complaint of stuffy nose for a long time is presented. Septal deviation is diagnosed. Ectopic tooth causing septal deformation is observed in the maxillary crest in computed tomograpy (CT) scans. Septoplasty is performed. Ectopic tooth is removed while septoplasty. Septal deviation is a well`-known common pathology, but ectopic tooth as an etiologic factor for septal deviation is rare.